Effect of Problem Based Learning (PBL) Models on Motivation and Learning Outcomes in Learning Civic Education - Vinni Dini Pratiwi; Wuri Wuryandani (Jurnal Pendidikan Indonesia, 2020)
This study aims to analyze the Problem Based Learning (PBL) learning model to develop learning motivation and learning outcomes in citizenship education learning. The use of PBL models in this study aims to help students develop investigative skills to be able to solve the problem at hand. The method in this study uses a quantitative approach with a quasi-experimental method and is used in the pre-test and post-test design groups. The subjects in this study were 34 students in SMP Negeri 6 Yogyakarta. The data analysis technique used "t" test with SPSS 16 assistance program and N-gain score test. The results of this study indicate that the PBL learning model on the values of the Pancasila material as a basis for the country and the national outlook on life significantly influence student motivation and learning outcomes. In this case, the PBL model can develop learning motivation and learning outcomes in the medium category.